Mapas de distribución de algas marinas de la Península Ibérica. IX. Saccorhiza polyschides (Lightf.) Batt. y Chorda filum (L.) Stackh. (Laminariales, Fucophyceae) - Izquierdo, José Luis; Gallardo, Tomás; Pérez-ruzafa, Isabel M. (Botanica Complutensis, 1995)
Sin resumen